Evaluation of agreement for radiographic lesions and risk for racing in thoroughbred yearling sale repository radiographs - Argue, Brodie J.; Ahern, Benjamin J. (Frontiers in Veterinary Science, 2024)
IntroductionThe veterinary yearling pre-sale repository radiographs have the potential to impact both vendor and prospective purchaser. The primary aim of this study was to determine inter-observer agreement for orthopaedic lesions identified in thoroughbred yearling repository radiographs. A secondary goal was to determine agreement when using a pre-defined risk rating classification.MethodsThree experienced specialist equine surgeons (2 ACVS & 1 FANZCVS) interpreted thirty repository radiographs once each for radiographic abnormalities. Each radiographic abnormality was given an associated risk assessment for future racing performance.ResultsThe use of a pre-defined risk rating grading scale resulted in good to excellent agreement as observers reached a consensus on risk ratings for lesions 97.1% of the time. The highest agreement was for the proximal interphalangeal joint and distal interphalangeal joint, with 99.9 and 98.2% agreement, respectively. The tarsal region was the joint with the highest disagreement with respect to pathology, with observers disagreeing 5.2% of the time.DiscussionThis study found that experienced veterinary surgeons reliably agreed on the absence of lesions but showed disagreement on the specific risk rating of common lesions.